Myocardial dysfunction in long‐term breast cancer survivors treated at ages 40–50 years. (6th November 2019) - Jacobse, Judy N.; Steggink, Lars C.; Sonke, Gabe S.; Schaapveld, Michael; Hummel, Yoran M.; Steenbruggen, Tessa G.; Lefrandt, Joop D.; Nuver, Janine; Crijns, Anne P.G.; Aleman, Berthe M.P.; van der Meer, Peter; Gietema, Jourik A.; et al.
Abstract: Aims: Anthracyclines increase heart failure (HF) risk, but the long‐term prevalence of myocardial dysfunction in young breast cancer (BC) survivors is unknown. Early measures of left ventricular myocardial dysfunction are needed to identify BC patients at risk of symptomatic HF. Methods and results: Within an established cohort, we studied markers for myocardial dysfunction among 569 women, who were 5–7 years ( n  = 277) or 10–12 years ( n  = 292) after BC treatment at ages 40–50 years. Left ventricular ejection fraction (LVEF) and global longitudinal strain (GLS) were assessed by echocardiography. N‐terminal pro‐brain natriuretic peptide (NT‐proBNP) was measured in serum. Associations between patient‐related and treatment‐related risk factors and myocardial dysfunction were evaluated using linear and logistic regression. Median ages at BC diagnosis and cardiac assessment were 46.7 and 55.5 years, respectively. Anthracycline‐treated patients ( n  = 313), compared to the no‐anthracycline group ( n  = 256), more often had decreased LVEF (10% vs. 4%), impaired GLS (34% vs. 27%) and elevated NT‐proBNP (23% vs. 8%). GLS and LVEF declined in a linear fashion with increasing cumulative anthracycline dose (GLS: +0.23 and LVEF: −0.40 per cycle of 60 mg/m 2 ; P  < 0.001) and GLS was worse for patients with left breast irradiation. The risk of NT‐proBNP >125 ng/L was highest for patients who received 241–300 mg/m 2 anthracycline dose compared to the no‐anthracycline group (odds ratio: 3.30, 95% confidence interval: 1.83–5.96). Conclusion: Impaired GLS and increased NT‐proBNP levels are present in a substantial proportion of young BC survivors treated with anthracyclines. Whether this will lead to future cardiac disease needs to be evaluated by longitudinal assessment.